2001
DOI: 10.1046/j.1365-8711.2001.04647.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorotational instability in a rotating liquid metal annulus

Abstract: Although the magnetorotational instability (MRI) has been widely accepted as a powerful accretion mechanism in magnetized accretion discs, it has not been realized in the laboratory. The possibility of studying MRI in a rotating liquid metal annulus (Couette flow) is explored by local and global stability analysis. Stability diagrams are drawn in dimensionless parameters, and also in terms of the angular velocities at the inner and outer cylinders. It is shown that MRI can be triggered in a moderately rapidly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 32 publications
7
154
0
Order By: Relevance
“…Here we generalize the derivation of the MRI dispersion equation (1) given in Kato, Fukue & Mineshige (1998) for the case of nonideal plasma with arbitrary kinetic coefficients ν and η (see also Ji, Goodman & Kageyama (2001)). …”
Section: Appendix A: Derivation Of the Dispersion Equation For Non-idmentioning
confidence: 88%
See 1 more Smart Citation
“…Here we generalize the derivation of the MRI dispersion equation (1) given in Kato, Fukue & Mineshige (1998) for the case of nonideal plasma with arbitrary kinetic coefficients ν and η (see also Ji, Goodman & Kageyama (2001)). …”
Section: Appendix A: Derivation Of the Dispersion Equation For Non-idmentioning
confidence: 88%
“…This problem has been addressed previously by different authors (see, e.g. Balbus & Hawley (1998); Sano & Miyama (1999); Ji, Goodman & Kageyama (2001); Balbus (2004); Islam & Balbus (2005); Pessah & Chan (2008), among others), aimed at studying various aspects of the MRI physics and applications. To keep the paper self-contained, we re-derive the basic dispersion relation in the general case and investigate its behaviour for different values of the magnetic Prandtl number P m = ν/η and the kinematic vicosity ν.…”
Section: Introductionmentioning
confidence: 99%
“…2. The experiment was designed to produce quasi-Keplerian flows of a liquid gallium alloy, GaInSn (Morley et al 2008) which would become unstable to the MRI in the presence of an applied solenoidal magnetic field (Ji et al 2001). To minimize the volume of GaInSn required for the MRI studies, the height of the cylinders is only twice the gap width between them, h/Δr = h/ (r 2 − r 1 ) ≈ 2.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that the β prescription by Richard & Zahn (1999), even if valid for the cyclonic evidence on which they based it, may not be valid for anti-cyclonic flow, in particular Keplerian flow. The Princeton MRI experiment is a Taylor-Couette device developed (Schartman et al 2009) to produce quasi-Keplerian flows in both water and a liquid gallium alloy to look for evidence of both SHI using water and the MRI using alloy (Ji et al 2001;Goodman & Ji 2002). The flows of interest are diagrammed in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the simplicity of this geometry, much work has been done to study the MRI for fluids between cylinders rotating with different angular velocities. Theory (Rüdiger & Zhang 2001;Ji et al 2001) and experiments (see Stefani et al 2009) revealed the possibilities to realize the MRI even in the laboratory.…”
Section: The Modelmentioning
confidence: 99%